Pengaruh Tahanan Kaki Menara Type Gantry Terhadap Terjadinya Back Flashover Pada Isolator Saluran 115 Kv Pt. Chevron Pacific Indonesia - Jefri Manik; Edy Ervianto; Nurhalim Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
This study describes analysis of tower footing resistance effected backflash voltage across a transmission line 115 kV insulator at PT. Chevron Pacific Indonesia. Back flashover analysis on insulator string provides ATP software for simulation. Analysis process is done by the entire transmission line parameter model such as a tower, lightning impulse, power line conductor and tower footing resistance. The factor of this study includes,front time of lightning stroke, and tower resistance. Simulations is done with lighting strike on the tower and mid-span with four types of impulse. To analysis of tower footing resistance effected back flashover across a transmission system insulator, Simulations are done by varying the tower footing resistance from 1Ω - 30Ω. Over Voltage on insulator for every tower footing resistance will be compare to critical flashover insulator (CFO) in order to obtain the maximum resistance is allowed to avoid the back flashover on insulator.Keyword: Tower fotting resistance, Back flashover, ATP, Insulator